Family violence in the new Russian realities: essence, types and reasons - R. M. Sadykov; N. L. Bolshakova (Вестник университета, 2022)
The article deals with the problem of domestic violence, which has its roots since ancient times and is quite common at the present time. The main types and forms of violence (physical, economic, sexual, psychological) are considered. In Russian society, women do not feel protected from the violence of spouses and other close relatives. In modern conditions, various forms of the use of force against women are common: domestic despotism, beatings, rape, sexual harassment. In many societies, family violence between a man and a woman is not perceived as a crime against society, but is a private matter of the family. It is believed that family members resort to physical violence in cases where they have no other opportunity to influence the family’s decision-making due to lack of authority. Psychological concepts have established a special role in the causes of violence of such factors as the weakening of instinctual control, frustration, aggressiveness, alcoholism, psychopathology. Sociological approaches focus on cultural norms that provoke violence, patriarchal social structure.